(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article investigates the issue of envisioning mathematical science of utilizing water, which is the second need of man, specifically, to decide the arrangement of an (a:b) division, to locate the number average mean, and to clarify the idea of fractions are shown through a “water counter”.